Uncovering the mechanism of Huangkui capsule in the treatment of diabetic kidney disease based on network pharmacology and experimental validation - Liu, Junhong; Li, Ziwei; Zhang, ZongYao; Shen, Zhongyuan (Scientific reports, 2025)
Diabetic kidney disease (DKD) is a main complication of diabetes mellitus. experimental in vitro validation and Network pharmacology were used in this study to explore the potential mechanism of Huangkui capsules (HKC) in treating DKD. First, we used CCK8 to analyze the optimal drug concentration of HKC. Next, we used flow cytometry, ELISA, Scratch test, and immunofluorescence to examine the apoptosis, oxidative stress, inflammatory factors, and fibrotic factors (FN and α-SMA) expression in HK-2 cells. Thereafter, in order to determine the potential molecular mechanisms underlying the therapeutic effect of HKC in DKD. Compounds contained in HKC were explored by UPLC-Q-TOF-MS/MS. SwissTargetPrediction was utilized for predicting potential gene targets of these compounds. OMIM, DisGeNet and GeneCards databases were employed to identify DKD-related genes. Meanwhile, the association of compounds with DKD genes was examined by protein-protein interaction, GO and KEGG analysis. Finally, molecular docking and molecular dynamics simulation were adopted for further validation. The results showed that HKC had 40 active ingredients, 1051 possible gene targets, and 133 DKD-HKC intersection genes. IL6, TNF, GAPDH, AKT1, PPARG, and TP53 were candidate hub genes by which HKC exerted its anti-DKD function based on molecular docking, molecular dynamics simulation and experimental results. To conclude, this study sheds more lights on the possible pharmacological activities of HKC in DKD and a foundation for further clinical application.